Using On -Line Media “The Jakarta Post News Report” to Teach English to Government Program Students of STISIP NH Jambi - Santi Hendrayani (Universitas Muhammadiyah Muara Bungo, 2020)
The use of media such as on-line media “The Jakarta Post” newspaper can support teachers and students in teaching English process. It will improve the students ability, skill, knowledge, attitude , language content, reading and vocabulary by providing on-line media ”The Jakarta Post “newspaper . The purpose of using on-line media can be used by the students in the classroom to develop their skill and also used as the learning resources. Teaching English to Government Program has many problem. Commonly the students lack ability in English because of education background and at this program English as Compulsory Subject. At STISIP NH Jambi learning English as Compulsory Subject (MKDU) mata Kuliah Umum. Based on Curriculum the students must follow the English Subject. In teaching process many students lack of ability in English. The students knowledge as long as Junior and Senior High School give the impact of teaching process. The writer for this paper would like to share the information , experience and the way to teach English as a compulsory Subject . The existence of On-Line Media The Jakarta Post for the Government Program. The writer do the technique observation( do direct observation of the students as the object), interview, documentations and library research. The result of the research showed that: The continuously of learning English by using on-line media must be formed to reach the target of mastering English and the students of English Program must relay that the existence of English for Government program must mastery English to can compete in employment field.